2017
DOI: 10.3390/ma10101204
|View full text |Cite
|
Sign up to set email alerts
|

Graded Microstructure and Mechanical Performance of Ti/N-Implanted M50 Steel with Polyenergy

Abstract: M50 bearing steels were alternately implanted with Ti+ and N+ ions using solid and gas ion sources of implantation system, respectively. N-implantation was carried out at an energy of about 80 keV and a fluence of 2 × 1017 ions/cm2, and Ti-implantation at an energy of about 40–90 keV and a fluence of 2 × 1017 ions/cm2. The microstructures of modification layers were analyzed by grazing-incidence X-ray diffraction, auger electron spectroscopy, X-ray photoelectron spectroscopy, and transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The feasibility of using ion implantation to improve the hardness and tribological characteristics of bearing steels is confirmed by the results of studies in [14]. Authors established the interrelation between physical and mechanical properties after alternate surface implantation with titanium and nitrogen ions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 82%
“…The feasibility of using ion implantation to improve the hardness and tribological characteristics of bearing steels is confirmed by the results of studies in [14]. Authors established the interrelation between physical and mechanical properties after alternate surface implantation with titanium and nitrogen ions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 82%
“…Moreover, the PT samples showed two peaks at 396.2 and 403.6 eV, corresponding to metal nitride [ 54 , 57 ] and N–O bonding [ 47 , 58 ], respectively, showing that a metallic nitride layer was formed during the N-PIII on the PT sample. Nitrogen atomic distribution along the depth of the M50 steel was reported to be in the range of 4–50 nm after N-PIII; the treatment increased the nano-indentation hardness and consequently improved the wear resistance [ 59 ]. Thus, the nitrogen implantation chemistry modification at the nanometric scale also affected the electrochemical behavior of the surface; this topic is discussed in detail in the following Section 3.3 .…”
Section: Resultsmentioning
confidence: 99%
“…Xiao demonstrated that the surface energy of materials decreased with decreasing grain size within an ultrafine grain size scope (<20 nm) through theoretical molecular dynamics [24]. Therefore, the wettability induced by N + and N + + Ti + high-energy ion implantation and high-energy ion coating of TiN was probably related to the formation of ceramic phases and an amorphous sublayer on the surface [25].…”
Section: Discussionmentioning
confidence: 99%